AVALIAÇÃO DA TRANSPARÊNCIA DAS INFORMAÇÕES DISPONIBILIZADAS NOS PORTAIS ELETRÔNICOS (WEBSITES) DOS TRIBUNAIS DE CONTAS BRASILEIROS COM O SUPORTE DA TEORIA DOS STAKEHOLDERS - Silva, Etonjones Oliveira da; Silva, Maurício Corrêa da (Perspectivas Contemporâneas, 2019)
Esta investigação tem o objetivo de analisar o nível de transparência das informações disponíveis nos portais eletrônicos (websites) dos Tribunais de Contas Brasileiros com o suporte da Teoria dos Stakeholders. Foi elaborada uma ficha de avaliação contendo trinta itens relacionados com informações que devem ser disponibilizadas (escala de 0 a 30). A avaliação ocorreu nos meses de fevereiro, março e abril de 2018 nos 33 portais eletrônicos (websites). Os principais resultados revelaram que o Tribunal de Contas do Estado do Espírito Santo obteve o nível 26, ficando na 1ª posição, seguido do Tribunal de Contas do Estado da Paraíba também com nível 26, mas por critérios de transparência das informações ficou na 2ª posição, em seguida ficaram o Tribunal de Contas da União (25) e o Tribunal de Contas do Estado do Paraná (25), nas posições 3ª e 4ª, respectivamente. Nas últimas posições ficaram o Tribunal de Contas do Município do Rio de Janeiro (9), o Tribunal de Contas do Estado do Amapá (8) e o Tribunal de Contas do Estado do Amazonas (8), respectivamente. Conclui-se que os stakeholders: Tribunais de Contas precisam rever os seus procedimentos para disponibilizar as informações determinadas pela legislação; os cidadãos possuem um instrumento de avaliação dos portais eletrônicos e os Poderes Legislativos e Executivos devem propor alterações na legislação para padronizar os processos para os tribunais de contas com regras para todos EVALUATION OF THE TRANSPARENCY OF THE INFORMATION MADE AVAILABLE ON THE WEBSITES OF THE BRAZILIAN COURTS OF ACCOUNTS WITH THE SUPPORT OF THE STAKEHOLDERS THEORY ABSTRACT The purpose of this investigation is to analyze the level of transparency of the information available on the websites of the Brazilian Courts of Accounts with the support of the stakeholders theory. An evaluation form was elaborated containing thirty items related to information that should be made available (scaling from 0 to 30). The evaluation occurred during the months of February, March and April of 2018 on the 33 websites. The main results revealed that the Court of Accounts of the State of Espírito Santo obtained a level of 26, ranking 1st, followed by the Court of Accounts of the State of Paraíba also with a level 26, but ranked 2nd due to criteria related to the transparency of the information. The Court of Accounts of the Union (25) and of the Court of Accounts of the State of Paraná (25) ranked 3rd and 4th respectively. The lower ranked courts were the Court of Accounts of the Municipality of Rio de Janeiro (9), the Courts of Accounts of the State of Amapá (8) and the Court of Accounts of the State of Amazonas (8), respectively. It is concluded that stakeholders: Courts of Accounts need to review their procedures to make the information determined by the legislation available; citizens have an evaluation tool for websites of the Brazilian courts of accounts and the Legislative and Executive Powers should propose changes in the legislation to standardize the processes for the courts of accounts with rules for all.